2017
DOI: 10.1111/ijd.13612
|View full text |Cite
|
Sign up to set email alerts
|

Review of treatment for alopecia totalis and alopecia universalis

Abstract: Alopecia areata (AA) is an autoimmune disease directed at the hair follicle. Although usually limited to patchy hair loss over the scalp (focalis), AA can present as total loss of scalp hair (totalis; AT) or as total loss of both scalp and body hair (universalis; AU). Management of AT and AU can be challenging, and although multiple treatment modalities have been explored, no therapy is currently FDA-approved. This review focuses on the evidence for current treatment options for AT and AU. The PubMed database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 49 publications
0
45
0
3
Order By: Relevance
“…1 Diagnosis of AT and AU typically indicates poor prognosis compared to patchy AA, and patients with these diseases are more likely to have treatment failure. [4][5][6][7] The long-term recovery rate of AT and AU is often described as <10% in the literature, [8][9][10][11][12] referring to studies published decades prior. 6,13 With the discovery of new therapies, it is possible that the prognosis of AT and AU has improved.…”
Section: Introductionmentioning
confidence: 99%
“…1 Diagnosis of AT and AU typically indicates poor prognosis compared to patchy AA, and patients with these diseases are more likely to have treatment failure. [4][5][6][7] The long-term recovery rate of AT and AU is often described as <10% in the literature, [8][9][10][11][12] referring to studies published decades prior. 6,13 With the discovery of new therapies, it is possible that the prognosis of AT and AU has improved.…”
Section: Introductionmentioning
confidence: 99%
“…Steroid treatment reduces inflammation around the hair follicle, allowing it to return to its normal growth cycle. However, despite its popularity, there is limited evidence to support the efficacy of oral steroids (11)(12)(13)(14)(15)(16). The greatest barrier to using steroids is the associated adverse reactions, especially with prolonged treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical use of cyclosporine in combination with steroids is advised only in refractory cases, given the severity of systemic adverse effects and lack of evidence (4). Also, DPCP immunotherapy is an option for treating recalcitrant AT/AU (11). The exact therapeutic mechanism of DPCP has not yet been elucidated; however, antigenic competition and decreased production of anti-hair-follicle antibodies are thought to play important roles (22).…”
Section: Discussionmentioning
confidence: 99%
“…15 A systematic review of treatments for alopecia totalis or alopecia universalis by Kassira et al identified 21 clinical trials and 19 case reports or retrospective studies, comprising a total of 1254 patients with AA, of whom 485 had alopecia totalis or alopecia universalis. 16 One retrospective case series of MTX was included that suggested useful regrowth in around 50% of patients. Lee and Lee searched PubMed until March 2017 and rated the evidence using the United States Preventive Service Task Force recommendation.…”
Section: Cochrane and Other Systematic Reviewsmentioning
confidence: 99%